Inventory Categorization and Operational Performance: A Supply Chain Analysis of Public Hospitals in Kenya - Okello, Sharone Adhiambo; Arani, Wycliffe; Sitienei, Carolyne Koech (Jobmer, 2020)
Performance of public hospitals is becoming a major concern to Kenyans. Public hospitals are currently facing the problem of balancing between overstocking and understocking of drugs. The main objective of this study was to determine the effect of inventory categorization practices on operational performance of public hospitals in Siaya County, Kenya. This study was anchored on Resource Based View Theory and Network Perspective Theory. The study adopted cross- sectional survey research design. The target population of the study was 106 with a sample size of 84 based on Yamane formula. The study adopted stratified proportionate and simple random sampling. Structured questionnaires and interview guides to collect primary data. Reliability was tested using split half analysis while validity was tested using expert judgment at an index of 0.70 Cronbach’s Alpha coefficient. Descriptive statistics were analyzed using frequency percentage, mean and standard deviation. Inferential statistics were analyzed using regression and correlation analysis. The hypothesis that, “there is no significant statistical effect of inventory categorization practice on operational performance of public hospitals in Siaya County” was rejected based on the findings which showed that inventory categorization had a statistically significant effect on performance of public hospitals in Siaya County with a coefficient of β=.754. The study concluded that the efforts that public hospitals put in inventory categorization as an inventory management practice would eventually become critical in realizing an improved operational performance in terms of service delivery for the patients. The study recommends that inventory Managers should categorize inventory with accurate forecasts.
Keywords: Inventory; Inventory Categorization; Operational Efficiency; Operational Performance